The epistemology of desire and the problem of nihilism - Hazlett, Allan (Oxford University Press, Incorporated, 2024)
This book is about the idea that goodness is the correctness condition for desire, in the same way that truth is the correctness condition for belief. Allan Hazlett argues that, given this similarity between desire and belief, desires, like beliefs, can both amount to knowledge and be justified or unjustified.